The issue of timely delivery of video traffic with controlled loss of quality - Barannik, V. V.; Kharchenko, N.; Tverdokhleb, V. V.; Kulitsa, O. (IEEE, 2016)
Need of development of new methods of coding and management of the bit speed of a video traffic for coordination with the capacity of a telecommunication network justifies.
Keywords: Bit speed; management of a video traffic; the pulsing traffic